Favipiravir Effectiveness and Safety in Hospitalized Moderate-Severe COVID-19 Patients: Observational Prospective Multicenter Investigation in Saudi Arabia - Al-Muhsen, Saleh; Al-Numair, Nouf S.; Saheb Sharif-Askari, Narjes; Basamh, Roaa; Alyounes, Banan; Jabaan, Amjad; Saheb Sharif-Askari, Fatemeh; Alosaimi, Mohammed F.; Alsohime, Fahad; Halwani, Rabih; Al-Saud, Haya (Frontiers in Medicine, 2022)
Objectives There are limited data on the efficacy and safety of favipiravir antiviral in coronavirus disease 2019 (COVID-19), particularly in the more progressed disease phase. This study aims to evaluate the favipiravir effect on reducing the length of hospital stay and in-hospital mortality among moderate and severe hospitalized COVID-19 patients. Methods A prospective, multicenter observational study was conducted that included moderate and severe hospitalized adult COVID-19 patients in four major regions (Riyadh (Riyadh), Eastern (Dammam), Al-Qassem (Buraydah), and Macca (Jeddah) of Saudi Arabia. For the primary outcome of all-cause mortality, a Cox proportional hazard analysis was performed. While the association between favipiravir use and length of hospital stay was determined using adjust the generalized linear model. The study was approved by the Central Institutional Review Board in The Saudi Ministry of Health (MoH) approval number (IRB # 20-85-M), and written informed consent was obtained from all human participants. Results This study included 598 moderate and severe covid patients, of whom 156 (26%) received favipiravir. Favipiravir treatment was associated with more extended hospital stays (14 vs 10 median, P=0.034) and higher mortality rate (aHR 3.63; 95% CI 1.06-12.45) compared to no favipiravir regimen. Despite lack of effectiveness, favipiravir use was only associated with higher diarrhoea adverse effects (12% vs 5%, P=0.002), but it did not affect the renal and liver profile of patients. Conclusion Favipiravir was ineffective in reducing the length of hospital stay and in-hospital mortality in patients with moderate and severe COVID-19.